EXPERT AND PRACTITIONER VALIDATION ON AUTHENTIC PROBLEM-BASED LEARNING TASKS IN PROMOTING STUDENTS’ CREATIVITY - Endah Tri Priyatni (Prodi PPkn Universitas Slamet Riyadi, 2021)
Fostering students’ creativity in learning is not effortless because the average learning activity is usually less challenging. Authentic problem-based learning is a learning model that is expected to foster students' creativity in education. This study aimed to examine expert and practitioner validation on authentic problem-based learning tasks prototype in promoting student creativity. The prototype product was displayed and simulated in virtual zoom and validated by 14 learning experts and 18 practitioners/teachers. The initial data were collected through self-evaluation using a questionnaire. The results showed that the use of real experiences as a learning stimulus could foster creative solutions, which are marked by the emergence of new, unusual ideas, imaginative ideas, new creations that have an impact on the development of student creativity.